2021
DOI: 10.1002/minf.202100156
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Reaction Yield for Buchwald‐Hartwig Cross‐coupling Reactions Using Deep Learning

Abstract: Chemical reaction yield is one of the most important factors for determining reaction conditions. Recently, several machine learning-based prediction models using high-throughput experiment (HTE) data sets were reported for the prediction of reaction yield. However, none of them were at a practical level in terms of predictive ability. In this study, we propose a message passing neural network (MPNN) model for chemical yield prediction, focusing on the Buchwald-Hartwig cross-coupling HTE data set. As an initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 37 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…Interestingly, however, regression models for Amine OOS split are superior with random forest methods. Consistent with previous work 11,15,[27][28][29][30][31] , random splitting of the data yields better models than any OOS scaffold splitting (Amine OOS, ArX OOS, Both OOS, Figure 4B, top). The performance of all three OOS cases for the stratified split was significantly inferior to the DRS strategy indicating that the model has a limited ability to extrapolate beyond molecules in its training set.…”
Section: Modellingsupporting
confidence: 88%
See 2 more Smart Citations
“…Interestingly, however, regression models for Amine OOS split are superior with random forest methods. Consistent with previous work 11,15,[27][28][29][30][31] , random splitting of the data yields better models than any OOS scaffold splitting (Amine OOS, ArX OOS, Both OOS, Figure 4B, top). The performance of all three OOS cases for the stratified split was significantly inferior to the DRS strategy indicating that the model has a limited ability to extrapolate beyond molecules in its training set.…”
Section: Modellingsupporting
confidence: 88%
“…The overall goal of predictive models is to predict reaction failures and successes with high fidelity. Literature reports suggest that models trained on random splits of HTE data generally perform well within the modeled datasets, 11,15,[27][28][29][30][31] an observation that is hypothesized to be a result of hidden patterns in the dataset and bias in its construction. 43 However, extending models to unseen structures is often difficult and limited by narrow substrate scopes.…”
Section: Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 13 On the other hand, topological descriptors accompanied by nonlinear machine learning (ML) models have sufficient predictive capability when trained on high-throughput experimental (HTE) data. 14 , 15 Although HTE data 16 18 provide the opportunity to analyze the comprehensive reaction space with high precision, the exhaustive combinations of substances under uniformly controlled experimental conditions are not usually available in laboratory-scale experiments for novel reaction development. Thus, methods for constructing highly predictive ML models trained on a small number of reactions are highly demanded.…”
Section: Introductionmentioning
confidence: 99%
“…Special attention in the issue was paid to the modeling of reaction properties. Thus, Sato et al [4] reported a deep learning-based descriptor-free model for yield prediction in important for medicinal chemistry Buchwald-Hartwig reaction. Genheden et al [5] proposed an interesting approach for predicting Buchwald-Hartwig reaction conditions, such as ligand, base, solvent, and (pre-)catalyst.…”
mentioning
confidence: 99%